2000
DOI: 10.1017/s0950268899004616
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of measles in Poland: prevalence of measles virus antibodies in the population

Abstract: WHO has adopted a goal of eliminating indigenous measles from the European Region by the year 2007. The strategy focuses on reducing the proportion of susceptible individuals in the population to low levels and maintaining these low levels of susceptibility. Routine vaccination against measles for children aged 13-15 months was introduced in Poland in 1975, and a second dose added in 1991. High coverage (> 95%) is achieved with both doses. In order to assess progress towards measles elimination in Poland, a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…9 In a study from Brazil, only 44% of children aged 9-15 years were antibody positive while a study from Poland observed that measles antibody was below the protective level in 22.5% of children. 24 In our study, measles antibody was detected in 80% children in the 13-24 months age group and 90% children in the 25-36 months age group, which gradually decreased to 62.5% in the 37-84 months age group. However, from the 85-96 months age group it increased again to 75% reaching 86% in the 97-108 months and 80% in 109-120 age groups.…”
Section: Detection Of Measles Iggsupporting
confidence: 47%
“…9 In a study from Brazil, only 44% of children aged 9-15 years were antibody positive while a study from Poland observed that measles antibody was below the protective level in 22.5% of children. 24 In our study, measles antibody was detected in 80% children in the 13-24 months age group and 90% children in the 25-36 months age group, which gradually decreased to 62.5% in the 37-84 months age group. However, from the 85-96 months age group it increased again to 75% reaching 86% in the 97-108 months and 80% in 109-120 age groups.…”
Section: Detection Of Measles Iggsupporting
confidence: 47%
“…The regression equations were quadratic (13/21), linear (5/21) as well as sigmoid (2). All laboratories using the EIA kit of Dade Behring or DiaSorin showed R 2 values of o0 .…”
Section: Rubella Resultsmentioning
confidence: 96%
“…Serological surveys allow the early identification of susceptible cohorts, allowing targeted interventions, e.g. catch-up campaigns to be undertaken [1][2][3][4]. Serological surveys can also be used to evaluate the impact of campaigns and ascertain elimination status [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the frequency distribution of (log) antibody levels in unvaccinated individuals, we defined as seronegative individuals whose measles-specific IgG antibody level were less than 100 IU/l. Seropositive individuals were stratified by cut-off levels of 255 [4], 500 [7] and 1000 IU/l [9].…”
Section: Classification Of Measles Antibody Statusmentioning
confidence: 99%
“…Serological surveys of specific antibody status in vaccinated populations provide valuable information to health authorities on the impact of the intervention on continued transmission [1,2], the distribution (by age and geographical location) of proportions seronegative [3][4][5], the risks of an outbreak [1,6], and the progress towards elimination [7]. Surveys that report on the level of detectable antibody, rather than presence or absence, may further inform on the likely distribution of sub-clinical, mild and typical measles re-infection and on the potential for community persistence of measles [3,4,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%